Assessment of Upper Central Incisor Crown Form - Senn LF; Lazos JP; Brunotto MN (2019)
Incisor crown form is thought to be associated with different periodontal features. Our hypothesis was that there are measures in Upper Central Incisor (UCI) that can be used to characterize its form. The aim of our study was to asses UCI crown dimensions in order to determine morphological groups. One hundred-fifty sound UCI were used without excessive evidence of incisal wear. On each crown several reference points were marked and some mesiodistal (md, MD) and axial diameters were measured using a digital caliper. A ratio between md and MD was made in order to asses dental forms. The UCI form was categorized in three groups (G1, G2 y G3) considering the upper limits of three intervals as cut-off point. The measurements were performed in a double blind fashion. Reliability of measurements were estimated by the Pearson correlation coefficient for each tooth, setting a value >0.8. The percent of UCI in each group was: G1 20.67%; G2 22.67%; and G3 56.67% (accuracy was 89% confirmed by linear discriminant method). Our results suggest that UCI morphology could be properly assessed through quantifiable methods. The md/MD ratio is simple, quantitative, and easily reproducible. It is a quantifiable definition of dental forms, based on characters that are not modified because of the position of the gingival margin or incisal wear. Hence, the GCC could help clinicians to assess tooth shape before performing restorative, orthodontic or surgical treatments.